The Effect Of Product Design, Product Quality, And Promotion On Customer Satisfaction Through Purchasing Decisions As An Intervening Variable - Micheallea Shalsabella Marendra; Sutrisno Sutrisno; Ratih Hesty Utami (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
The purpose of this study was to determine the factors that affect customer satisfaction at the Jati Putra Mandiri Indonesia company. PT Jati Putra Mandiri is experiencing problems with customer satisfaction with the products offered. The independent variables used in this study are product design (X1), product quality (X2), promotion (X3) and the intervening variable in this study is the purchase decision. The population and samples used in the study were all customers at PT Jati Putra Mandiri Indonesia, totaling 148 respondents. The research uses quantitative methods where the analysis technique used is Partial Least Square (PLS) with SmartPls 3.2.9 software. The results of the analysis show that product design has no effect on purchasing decisions and customer satisfaction. Product quality has a positive influence on purchasing decisions and customer satisfaction, promotion has a positive effect on purchasing decisions and customer satisfaction. Then purchasing decisions are able to mediate the role of product quality on customer satisfaction, while product design and promotion are not significant. Thus, it can be concluded that the factors that influence customer satisfaction in this study are product quality, promotion, and purchasing decisions. Therefore, it is recommended for companies to maintain product quality and improve promotions and purchasing decisions.